KARAKTERISTIK WANITA USIA SUBUR DENGAN TINDAKAN PENCEGAHAN KANKER SERVIKS - Supatmi Supatmi (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2020)
AbstractBackground:  The awareness of Indonesian women to carry out early detection of cervical cancer on a regular basis have been still low. Cervical cancer can be prevented and cured by taking early detection measures because it has a long preinfassive phase. Cervical cancer prevention measures are influenced by several factors including age, education level, occupation and parity, Aims:   analyze the characteristics of women of childbearing age with cervical cancer prevention measures (HPV, IVA and Pap smear immunization) Methods: Quantitative analytic research design with cross sectional approach. The population was 193 women of fertile age in RW 9 Kelurahan Kapasan Surabaya with n Cluster Samples, the sample was 130 WUS. The research instrument used a characteristic questionnaire and cervical cancer prevention measures with a Dichotomy Question. The research variables were WUS cataristic and cervical cancer prevention behavior. Analysis with Chi-Square with a significance level of 0.05Results:  There was a relationship between age and HPV immunization (p = 0.066) and pap smear (p = 0.058), IVA action had not relationship (p = 0.770), education was related to HPV immunization (p = 0.346). IVA (0.005) was not related to pap smears = 0.603) Occupation was related to HPV immunization (p = 0.280), IVA (p = 0.000) and pap smears (p = 0.216), parity was related to HPV immunization (p = 0.003) ) and Pap smear (p = 0.117) meanwhile parity had not relationship with IVA (p = 0.839). Studying the characteristics of WUS is a first step to increase preventive efforts for cervical cancer both primary and secondary prevention   Keyword:  Characteristics of WUS, Prevention, Cervical Cancer